Factors causing rework and their impact on projects’ performance in Egypt - Al-Janabi, Assim Muwafaq; Abdel-Monem, Mohamed Shawky; El-Dash, Karim Mohamed (Journal of Civil Engineering and Management, 2020)
The Egyptian construction industry suffers from severe delays and cost overruns. Rework is a prime cause of this challenge. Therefore, the objective of this study to identify the root causes of rework for Egyptian construction projects and their impact on the project duration and cost. An extensive literature review has been done to identify the most common factors affecting rework. Hence, eighty-seven factors were identified and categorised into ten groups. Structured interview technique was adopted to get the opinions of 67 Egyptian construct professionals for nineteen different construction projects. Total Importance Index of Rework Impact (T.I.I.R.I%) was used to analyse and rank rework factors. Accordingly, the most critical five rework factors are economic situation for the country, schedule compression, design changes, specifications change, and inadequate feasibility study. Based on the survey results, the project stakeholders should consider the critical rework factors during the planning stage and before the project execution, to eliminate or reduce the occurrence and impact of rework causes and to improve the performance of the projects. This paper provides state of the art for rework causes and their effects on construction projects performance, and it can be beneficial for both practitioners and researchers for future work.